The Economic Impact of Olympic Games: Evidence from Stock Markets - Christian D. Dick; Qingwei Wang (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
By means of an event study of stock market reactions to the announcement of the Olympic Games host cities, we find a significant and positive announcement effect of hosting the Summer Games, with a cumulative abnormal return of about 2% within a few days. We do not find any significant results for the Winter Games. Neither do we detect a significant impact when bidders lose the competition. Our results differ from those of a similar study by Mirman and Sharma (2008), who find that the Winter Games are subject to a significantly negative announcement impact, while the Summer Games are not. Our results, however, rely on a larger sample of 15 Olympic events and are obtained by assessing the abnormal returns after the announcement against a ?business?as?usual" situation (instead of testing the difference between winner group and loser group). Our findings are in line with economic intuition, since the Summer Games represent a larger event and are thus more likely to have a significant impact. We also find that among the winners, small economies tend to have greater cumulative abnormal returns than their large peers.
Keywords: G14; L83; 330; Olympic Games; economic impact; event study; stock markets; Sportereignis; Großveranstaltung; Sport; Ankündigungseffekt; Börsenkurs; Aktienmarkt; Welt; Olympic Games <1; 1896 - 29; 2008>